Aplicação da metodologia FMEA na gestão de risco no planejamento estratégico da UFSCar - Recchia, Wania Maria (2016)
This paper proposes a system to help the managers of a Federal University, aiming to identify and to monitor the risks that might appear during the creation of its Plan of Management and or Strategic Plan. For this, the concepts of risks and risks management are developed based on several methodologies used, mainly, in the private sector. Thus, an adaptation of those methodologies was performed in a public institution, which has many characteristics, such as: not seeking profit, vision of equity, multicriterial decision making, among others. In this scenery, a system based on the FMEA was developed to help managers during the process of elaboration of the Plans of management and of its details in the Strategic Plan. This action has the purpose to apply on a preliminary stage of reflection, the FMEA, which must occur in the planning moment, once it will reveal the risks of implementing the proposed actions. The results of the case study in the Strategic Planning pointed out that the actions are still in progress, after application of FMEA, were classified as moderate to high level, a fact that points to the need for treatment of the risks involving the action, with the purpose that the objectives were achieved within the planning period. Or even, it could happen a preliminary analysis of the action to scale their placement in PE with compliance just steps to involve other future periods efforts. However, the systematic application of the developed model should be adjusted to provide the best facility of use.